Innowacyjność regionów Polski na tle europejskiej przestrzeni regionalnej ze względu na rozwój sektora usług - Strahl, Danuta (Innovation in Polish Regions Against the Background of European Regional Space in the Context of the Services Sector Development, 2006)
The article presents an assessment of the services sector development in the European regional space, with a division into market and non-market services. The basic measure used in the assessment of 248 NUTS-2 regions is the ratio of employment in services. The article aims to verify the hypothesis that regions with well-developed services are also well-developed in terms of GDP per capita. Against this background, the 16 Polish regions (provinces) are analysed. The analysis is based on a classification of hierarchic objects with positional statistics that allows ranking. The Polish regions fall within the classes of the lowest ratios of employment in services and also the lowest values of GDP per capita. Poland is in the group of countries with the lowest development of services sector, together with the Czech republic, Hungary, Lithuania, Latvia, Slovakia and Slovenia.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 27-36